2013
DOI: 10.1089/dna.2012.1949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methylation of MGMT (O6-Methylguanine-DNA Methyltransferase) Gene Promoter in Sporadic Colorectal Cancer

Abstract: The DNA repair gene O⁶-methylguanine-DNA methyltransferase (MGMT) is frequently methylated in colorectal cancer (CRC). The aim of this study was to demonstrate that MGMT methylation may be one of the candidate mediators of field cancerization in the colon mucosa. Therefore, quantitative methylation-specific polymerase chain reaction was performed on tumor itself and additional samples of 5 and 10 cm away from the tumor in 40 CRC patients. Moreover, colon mucosa was examined from 30 cases with no evidence of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Several previous reports of the literature suggest that MGMT hypermethylation results in gene silencing and increased rate of mutations in normal colonic mucosa that might represent an initiating step in the development of mismatch repair-deficient CRC. [22][23][24][25] We also observed an age-related increase in MGMT methylation in CRC tissues in agreement with previous reports by Tserga et al 26 that showed a correlation between age and MGMT promoter methylation in breast cancer specimens, and Menigatti et al 21 that showed an age related increase of MGMT methylation in healthy colonic mucosa samples. CDKN2A was methylated in 29% of CRC samples and both RASSF1A and hMLH1 in 16.8% of them; by contrast, they resulted methylated only in a few healthy mucosa tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous reports of the literature suggest that MGMT hypermethylation results in gene silencing and increased rate of mutations in normal colonic mucosa that might represent an initiating step in the development of mismatch repair-deficient CRC. [22][23][24][25] We also observed an age-related increase in MGMT methylation in CRC tissues in agreement with previous reports by Tserga et al 26 that showed a correlation between age and MGMT promoter methylation in breast cancer specimens, and Menigatti et al 21 that showed an age related increase of MGMT methylation in healthy colonic mucosa samples. CDKN2A was methylated in 29% of CRC samples and both RASSF1A and hMLH1 in 16.8% of them; by contrast, they resulted methylated only in a few healthy mucosa tissues.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, field cancerization due to MGMT promoter methylation has not been reported so far. MGMT field cancerization has, however, been detected in colorectal cancers [ 14 , 41 ] and oral squamous cell carcinomas [ 42 ]. Aberrant methylation in tissue adjacent to breast tumor has already been reported previously for RASSF1A [ 20 , 21 ] and HIN-1 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported that MGMT methylation is a useful marker to detect early stages of CRC [34,35]. Kang et al .…”
Section: Discussionmentioning
confidence: 99%